PENGARUH GAYA HIDUP DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MELALUI CASH ON DELIVERY (COD) PADA PELAKU UMKM DI SIDOARJO - Qurrota A'yun Qurrota A'yun; Riris Maghfirotul Fitriyah Riris Maghfirotul Fitriyah; Moh Argy Hariran H Moh Argy Hariran H; Laily Muzdalifah Laily Muzdalifah (Universitas Nahdlatul Ulama Sidoarjo, 2021)
The purpose of this study is (1) to find out the influence of lifestyle on purchasing decisions through cod (cash on delivery) on MSME actors in Sidoarjo, (2) to find out the influence of consumer perception on purchases through cod (cash on delivery) on MSME actors in Sidoarjo. Type of quantitative research with a descriptive approach. This research place was conducted in Sidoarjo district using purposive sampling method with a total of 100 respondents. Data analysis techniques using Path Analysis. Based on the results of the analysis can be concluded that the lifestyle and perception of consumers affect purchasing decisions through cod (cash on delivery) to MSME actors in Sidoarjo. This shows that lifestyle and consumer perception can improve purchasing decisions through cod on MSME in Sidoarjo.